The forge [videorecording (DVD)] - Kendrick, Stephen, 1973-; Kendrick, Alex, 1970-; Arnett, Cameron, 1960-; Shirer, Priscilla, 1974-; Kennedy, Aspen, 1995-; Abercrombie, Karen, 1956-; Stallings, T. C., 1977-; Leffew, Zack, 1992-; Scott, Bob M. (Sony Pictures Home Entertainment, 2024)
Isaiah Wright has some growing up to do. A year out of high school with no plans for his future, Isaiah is challenged by his single mom and a successful businessman to start charting a better course for his life. Through the prayers of his mother and biblical discipleship from his new mentor, Isaiah begins to discover God's purpose for his life is so much more than he could hope for or imagine.